2020
DOI: 10.31234/osf.io/72uav
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Frequency of engagement with legal UK youth gambling products is associated with adult disordered gambling

Abstract: The potential effects of exposing children aged under 18 to gambling is an area of concern for researchers and policy-makers around the world. The UK is rare in that it allows for a number of gambling products to be legally used by people under the age of 18. The present research is a retrospective cross-sectional study of 1,052 adult UK gamblers, aged 18 - 40. Five legal youth gambling products were considered: Category D fruit machines, the National Lottery, National Lottery scratchcards, coin push machines,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 16 publications
2
4
0
Order By: Relevance
“…This may also be because crane grab machines are the only product out of the five tested that does not yield monetary winnings. The results for levels of recalled usage (hypothesis 2) confirm what was found in an earlier study (Newall et al, 2020). Like the present results, that earlier study also found a statistically significant relationship between recalled scratchcard engagement and adult disordered gambling.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This may also be because crane grab machines are the only product out of the five tested that does not yield monetary winnings. The results for levels of recalled usage (hypothesis 2) confirm what was found in an earlier study (Newall et al, 2020). Like the present results, that earlier study also found a statistically significant relationship between recalled scratchcard engagement and adult disordered gambling.…”
Section: Discussionsupporting
confidence: 91%
“…The authors are only aware of one previous attempt to explore associations between recalled rates of legal youth gambling engagement and adult disordered gambling (Newall, Russell, Sharman, & Walasek, 2020). That study found that higher rates of recalled usage for each product were associated with adult disordered gambling.…”
Section: Introductionmentioning
confidence: 99%
“…However, higher risk-taking in youth is associated with addiction vulnerability later in life 29,31,35 . Thus, adolescent loot box purchasing may have implications for future risk-taking behaviour 36,37 , as risk is an inherent part of loot box engagement and loot box use is considered by some to be a form of risk behaviour 38,39 .…”
Section: Loot Boxesmentioning
confidence: 99%
“…Younger lottery-only players are more likely to report problems as a result of their use of lottery play compared to older players 2 . Early scratchcard play also poses long term risks, where playing scratchcards when 16 or 17 predicts adult gambling problems 9 .…”
Section: Rationale and Literature Reviewmentioning
confidence: 99%